Thermal comfort evaluations in school building in Shah Alam / Norazimah Zainal - Zainal, Norazimah (Faculty of Architecture, Planning and Surveying, 2015)
Nowadays, rapidly development in urban area can affect local climate. This micro-climate change may disturb the surrounding environment, including schools. However, the investigations and evaluations of thermal comfort in learning and teaching environment are very limited, especially for school building. Thermal comfort is defined as “that condition of mind, which expresses satisfaction with the thermal environment” (ISO Standard 7730 in 1994). Thermal comfort is affected by indoor temperature causes by heat, humidity, air velocity and human metabolism. Thus, Malaysian standard was suggesting the thermal comfort range for conventional building. Any gains or losses outside this range, the heat will cause discomfort. These studies reports on the findings of a preliminary survey conducted to identify and investigate the thermal comfort evaluations in school building in Shah Alam using Velocicalc meter instrument. The main objective of this study is to study the criteria for thermal comfort performance in school building in Shah Alam, Selangor, to assess the thermal 'comfort performance in classroom in school building and lastly researcher will recommend the best practice to achieve thermal comfort performance in school building. The study was conducted at 3 number of school, which are SMK Seksyen 7, SMK Seksyen 24 and SMK Sultan Salahudin Abdul Aziz Shah. Besides using Velocicalc Meter, sample of questionnaire are distribute to student at each school to assess the student perception on thermal comfort performance of their classroom.